Contamination by pathogens in street food: Systematic review (Research, Society and Development, 2021)
In a globalized era, the lack of time, convenience, individual preferences and people's own lifestyles, mean that, each year, the number of meals eaten outside the home grows. Although this movement is an economic alternative, this practicality has caused an increase in the number of food outbreaks. This literature review aims to address the main pathogens and problems found in street foods. Reference data indicate that street food contamination is frequent and a risk to public health. A plan of interventions and training of street vendors is needed, regarding the correct hygiene of all production processes, to ensure food safety for consumers. Furthermore, an adequate basic structure for the seller is essential to prioritize the quality of food supply.